Pengaruh Penggunaan Mind Mapping Terhadap Motivasi Belajar dan Retensi Siswa pada Pelajaran IPA Kelas VIII MTs Maraqitta’limat Tembeng Putik - Ika Mas’adatul Barroh; Mukminah Mukminah; Edi Muhamad Jayadi (Pusat Riset dan Inovasi Nasional, 2024)
This research was motivated by the imbalance between the amount of science subject matter and the time available, as well as the lack of facilities and infrastructure that support learning in schools. The aim of this research is to determine the effect of using mind mapping on student learning motivation and retention in class VIII biology lessons at MTS Maraqitta’llimat Tembeng Putik in Wanasaba, East Lombok. The method used in this research is Quasi Experiment. The population in this study was all class VIII MTs Maraqitta'limat Tembeng Putik, while the sample in this study was class VIII B as the experimental class and class VIII A as the control class taken using the cluster random sampling method. The data in this study was collected by providing a questionnaire with 30 statements to measure students' learning motivation and providing a test instrument with 20 short description questions to measure student retention. The data obtained was then analyzed using the Manova Test (Multivariate of Variants) with the help of SPSS. 24. The results of the hypothesis test show a significance value of 0.000. The significance value is less than 0.05. Based on these results, it can be concluded that firstly, the use of mind mapping has an effect on students' learning motivation in class VIII biology learning at MTS Maraqitta'limat Tembeng Putik lesson 2022/2023. Second, the use of mind mapping has an effect on student retention in class VIII biology learning at MTs Maraqitta'limat Tembeng Putik lesson 2022/2023.